Alcohol, tobacco and other drug concerns of newly arrived 'CaLD' (culturally and linguistically diverse) women in Perth - Lee, Susan Kaye (Curtin University, 2008)
Womens Health Services (WHS) in Perth provides medical services, counselling, information, community talks and workshops, referral, and outreach to women in Western Australia. WHS works with women from over sixty different nationalities, including many newly arrived migrants and refugees. New arrivals access a wide range of WHS programs, but at the time the current study was developed few ethnic women attend the alcohol and other drug (AOD) services offered by the organisation. To address this a needs assessment was conducted with newly arrived women (0 to 5 years in Australia). The needs assessment examined the use of alcohol and other drugs by newly arrived women, the barriers that prevent women from accessing alcohol and other drug (AOD) services and explored the types of services and programs newly arrived women wanted.Method. The needs assessment used both qualitative and quantitative methods. Twenty two service providers working with newly arrived migrant and humanitarian entrant women were either interviewed individually or attended a focus group. The views and experiences of 26 newly arrived women from a variety of culturally and linguistic backgrounds were also collected through one-on-one interviews (n=6) and through focus groups (n=5). The information gathered from these interviews and discussions informed the design of a questionnaire that was administered to 268 newly arrived women. All women participating in the project were 18 years of age or more, Australian citizens, permanent Australian residents or in the process of being granted permanent residency and had lived in Australia 5 years or less.Findings Regarding Tobacco and Alcohol Use. Australian cultural attitudes had had an impact on newly arrived women's alcohol and other drug use. Some impacts were positive, for example, increasing restrictions and the decrease in acceptability of smoking in public places along with strong educational messages about the risk of smoking had influenced some women to quit since coming to Australia. Unfortunately, not all Australian cultural attitudes had a positive impact on newly arrived women. Just under one third of the women (31.7%) who drank alcohol were drinking more alcohol since coming to Australia. Reasons for drinking more alcohol were varied and included alcohol being cheaper in Perth than in their own countries, socialising with Australians who drank alcohol, and using alcohol as a way of coping with stress. However, it is important to note that only a very small percentage of the newly arrived women participating in the needs assessment drank at levels considered risky or high risk for either short term or longer term harm. The vast majority of respondents surveyed did not smoke (n=207; 77.2%) and did not use alcohol (n=201; 76.1%), often due to cultural or religious reasons.Other Results. Other findings of the needs assessment included: • Over 21% of newly arrived women responding to the survey had been put in fear by some one under the influence of alcohol and/ or drugs. Nearly 17% of women responding to the survey had been verbally abused by some one under the influence of alcohol and/ or drugs. • More than one third of the women responding to the survey indicated that they wanted information and support on family violence. • Over 40% of the women responding to the survey wanted information and support for depression. • Forty women (14.9%) responding to the survey wanted support for husbands or children that were drinking too much alcohol.A surprising finding was the high level of interest in women's only exercise classes and opportunities to participate in other types of physical activity Two thirds of questionnaire respondents said that exercise was a priority for them. Subsequent feedback sessions with newly arrived women about the results of the needs assessment confirmed the need for opportunities to participate in a variety of physical activities in a safe, affordable, women only environment where childcare was available.Understandings of Alcohol and Other Drug Services. Participants in the study appeared to have a poor understanding of what AOD services were, different types of treatments and models that could be used, who was entitled to access them (not just the alcohol or other drug user), the associated costs and fees, and whether or not the police would become involved. There was a significant lack of understanding by service providers working with newly arrived women about eligibility to access alcohol and drug services and what assistance and support these agencies could provide either to women using alcohol and other drugs or to family and friends impacted by another's drug use. Few service providers asked their clients any questions about alcohol or other drug use on a regular basis.The findings from the needs assessment have been used to improve programs and services with newly arrived women at WHS. These have included the addition of a specific alcohol and other drugs program for women from culturally and linguistically diverse backgrounds with a focus on prevention activities as well as opportunities for newly arrived women to participate in a variety of physical activity classes.